Family Communication Scale (FCS) - Chavez Laurente, Dayana Carolina (2020)
One of the most important systems in society is the family, and with it the communication that arises between members. For this reason, the psychometric evidence of the Family Communication Scale (FCS) was analyzed. The sample was of 210 Peruvian university students, 46.19% were from public universities and 53.81% were from private universities. The sample was made up of 44.29% men and 55.71% women, with participants from the Costa region(85.25%), Sierra (11.44%) and Selva (3.31%). The reagents indicated appropriate adjustment indexes. In addition, confirmatory factor analysis (CFA) showed the validity of the internal structure and the unidimensionality of the scale, providing the following results: X2= 79,370, gl =35, X2/gl = 2.26, IFC = .945, TLI = .929, RMSEA = .078, SRMR = .046. In turn, the FCS scale has a positive correlation with the family functioning scale and need for social approval; however, it has an inverse relationship with the filio-parental violence scale. On the other hand, the reliability was of α .939 and ω of .94, thus representing the validity of the instrument. Finally, invariance was presented, taking into account gender and university management, resulting in participants understanding and responding similarly to the questionnaire.